Paracas en el valle de Chincha: nuevos datos y explicaciones - Tantaleán, Henry (2013)
This article summarizes and discusses the results of our recent archaeological research in the middle valley of Chincha duringthe Late Paracas period (circa 400 BC-100 BC). We present archaeological data (architecture, geoglyphs, ceramics, textiles, etc.)recovered from research on sites in the middle valley in the area including to Cerro del Gentil and the El Mono archaeologicalcomplex. These data, along with previous work by colleagues in the last two generations, allow us to propose new perspectives about development of social complexity in this southern Peruvian coastal valley.